Immunotherapy and Hormone-therapy in Metastatic Breast Cancer: A Review and an Update - Nicolini, Andrea; Carpi, Angelo; Ferrari, Paola; Mario Biava, Pier; Rossi, Giuseppe (Current Drug Targets, 2016)
Historically, antiestrogen is the first targeted therapy used in breast cancer treatment. In fact, its rationale lies in the molecular pathways elucidated by basic research. In estrogen receptor (ER)-alpha positive metastatic breast cancer patients, hormone-therapy remains the first option of treatment. While tamoxifen concomitant with suppression of ovarian function with luteinizing hormone releasing hormone (LHRH) agonists is the standard first line treatment in premenopausal, third generation aromatase inhibitors (AIs) are the first line standard hormone therapy in postmenopausal. However, the development of acquired resistance during antiestrogen therapy continues to be a central clinical problem. This review provides an update on the antiestrogen action and report on immunological treatment of the advanced disease by some cytokines. Interleukin-2, interleukin-12 and interferons used alone or in combination demonstrated an anti-tumor action directly and/or through synergism with antiestrogens. A rationale for the addition of interferon-beta and interleukin-2 to antiestrogens is described. Furthermore, we summarize and interpret the clinical and laboratory data of a recent long-term hormone- immunotherapy study in metastatic endocrine dependent breast cancer patients. Prospective randomized trials are necessary to confirm some recent promising results based on an immunological approach in addition to antiestrogens to overcome or delay acquired hormone resistance.
Keywords: hormone therapy